Mandibular symmetry in participants with a unilateral cleft lip and palate - Ozge Uslu-Akcam; Ufuk Toygar Memikoglu; Mehmet Okan Akcam; Mehmet Birol Ozel (Wolters Kluwer Medknow Publications, 2017)
Context: Facial asymmetry has been reported to be a typical morphological characteristic of unilateral cleft lip and palate (UCLP). Posteroanterior cephalometric radiographs have shown that in addition to an asymmetrically developed nasomaxillary complex, children with UCLP may also have distorted mandibles. Aims: The aim of this retrospective study was to evaluate mandibular symmetry in participants with a complete unilateral left cleft lip and palate (ULCLP) using panoramic radiographs. Subjects and Methods: Pretreatment records of 163 participants (84 ULCLP, 79 Angle Class I without a cleft; mean age: 12.9 ± 3.5 years) were retrieved from the orthodontic department archives. A total of ten anatomic landmarks were marked on panoramic radiographs, and measurements were performed using the PORDIOS software. Statistical Analysis Used: Intra- and inter-group differences were analyzed using Student's t-test. Results: Mandibular right and left ramus, total ramus, condylar, and mandibular molar alveolar heights were significantly shorter in the ULCLP group when compared to controls (P < 0.05 to P< 0.001). In the ULCLP group, mandibular and corpus lengths were shorter on the left side (P < 0.05), whereas in the control group, mandibular and corpus lengths and ramal, condylar, and molar alveolar heights were shorter on the right side when compared to the left side. In addition, ramus/corpus angles were significantly larger in the ULCLP group when compared to the control group (P < 0.001). Conclusions: Mandibular asymmetry exists to varying extents in ULCLP patients and is characterized mainly by smaller cleft-side dimensions. Discrepancies in left-right mandibular dimensions also occur in normal participants.